2018
DOI: 10.1038/s41598-018-20821-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-adipogenic effects of KD025 (SLx-2119), a ROCK2-specific inhibitor, in 3T3-L1 cells

Abstract: Adipose tissue is a specialized organ that synthesizes and stores fat. During adipogenesis, Rho and Rho-associated kinase (ROCK) 2 are inactivated, which enhances the expression of pro-adipogenic genes and induces the loss of actin stress fibers. Furthermore, pan ROCK inhibitors enhance adipogenesis in 3T3-L1 cells. Here, we show that KD025 (formerly known as SLx-2119), a ROCK2-specific inhibitor, suppresses adipogenesis in 3T3-L1 cells partially through a ROCK2-independent mechanism. KD025 downregulated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 52 publications
8
32
0
Order By: Relevance
“…25,26 Further, it is reported that differentiation starts with the induction of Cebpb at an early stage, during which cells begin to express Pparg and Cebpa. 28,29 Our results are consistent with those of previous reports (Fig. 5).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…25,26 Further, it is reported that differentiation starts with the induction of Cebpb at an early stage, during which cells begin to express Pparg and Cebpa. 28,29 Our results are consistent with those of previous reports (Fig. 5).…”
Section: Discussionsupporting
confidence: 94%
“…Overall, 3T3-L1 cells were originally developed by clonal expansion from murine Swiss 3T3 cells 27 and have been widely used as preadipocytes in studies of adipocyte differentiation. [27][28][29] In our hands, LAT-A and PGF 2a prevented the accumulation of lipid droplets in 3T3-L1 cells and inhibited adipogenesis ( Figs. 3 and 4).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Indeed, its therapeutic potential has been explored in fibrotic disease, 15 focal cerebral ischemia, 16,61,62 and auto-immune disease. 67 However, we have noticed some differences between our study in SV cells with the reported study in 3T3-L1 cells: (a) KD025 treatment reduced total ROCK activity reflected by reduced p-MLC and p-cofilin levels in SV cells, but not 3T3-L1 cells, (b) KD025 treatment disrupted actin cytoskeleton in SV cells, but not 3T3-L1 cells, (c) KD025 reduced adipogenesis on terminally differentiated SV cells, but not on terminally differentiated 3T3-L1 cells, and (d) the effects on beige adipogenesis were not examined in 3T3-L1 cells. Importantly, both dose-and time-dependent analyses ( Figure 7E; Figure S8A) helped to dissociate the pro-beige adipogenic (mediated by ROCK2 inhibition) and anti-adipogenic (targets are not clear) actions of KD025.…”
Section: Discussionmentioning
confidence: 99%
“…Upon administration, KD025 binds to and thereby inhibits the serine/threonine kinase activity of ROCK2. Furthermore, KD025 has been reported in various studies to be a potential candidate for the treatment of obesity, insulin resistance [23][24][25][26], rheumatoid arthritis, systemic lupus erythematosus [27], inflammatory bowel disease [28], chronic autoimmune disorders, chronic graft-versus-host disease [29], and fibrosis [30], as well as protection of the blood-brain barrier during thrombolysis [31]. In several phase 1 clinical trials in healthy volunteers, oral administration of KD025 was well tolerated and produced no significant adverse events, including cardiovascular side effects [19,32].…”
Section: Introductionmentioning
confidence: 99%